Perlindungan Hukum bagi Pemegang Saham: Menggali Hak dan Risiko dalam Perseroan Terbatas - Zahra, Humaerotuz; Putri, Ambar Krisna; Tambunan, Henri Marusaha (Media Hukum Indonesia (MHI), 2024)
This article discusses a legal entity in the business world known as a limited liability company (PT), focusing on the rights and obligations of shareholders, the Board of Directors, and the Board of Commissioners within the context of limited liability as regulated by Law Number 40 of 2007 on Limited Liability Companies (UUPT). As a legal entity, PT has distinct characteristics, including a clear separation between the assets of the company and the personal assets of its management and shareholders. Shares in a PT function as proof of capital ownership, granting economic and proprietary rights to shareholders without directly imposing personal responsibility for the company's obligations. There is a division between majority and minority shareholders, which influences decision-making in the General Meeting of Shareholders (RUPS), the highest governing body in a PT. This article also outlines legal protections for shareholders as well as various legal risks they may face. The research method used is a qualitative approach involving literature analysis and legal review to understand the challenges and legal solutions in the PT sector.